Business acumen dan perilaku kerja inovatif pada industri energi: Menguji peran motivasi intrinsik dan person job fit: Business acumen and innovative work behaviour in the energy industry: Examining the role of intrinsic motivation and person job fit - Iqbal, Rofiq; Etikariena, Arum (Persona:Jurnal Psikologi Indonesia, 2024)
In the upcoming era of sustainability, energy companies face various environmental issues, necessitating innovation from their employees to tackle these challenges. This study aims to identify whether intrinsic motivation moderates the indirect effect of Person Job Fit mediating the relationship between Business Acumen and Innovative Work Behaviour. This study was conducted at a publicly listed energy sector company, involving 271 permanent employees who have worked for at least one year. Convenience sampling was used to select the participants. The measurement tools included Business Acumen (α = 0.95), Person-Job Fit (α = 0.79), intrinsic motivation (α = 0.80), and innovative work behavior (α = 0.80). Data analysis using Process Macro Model 14 showed that Business Acumen (BA) has a significant direct effect on both Person-Job Fit (P-J Fit) and Innovative Work Behavior (IWB). However, intrinsic motivation does not significantly moderate the indirect effect of P-J Fit. Nevertheless, P-J Fit is proven to mediate the relationship between BA and IWB at certain levels of intrinsic motivation. This study significantly contributes to the literature and practical implications for companies in enhancing employees' innovative behavior.